2014
DOI: 10.1177/089875641403100104
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic Therapy of a Mandibular Canine Tooth with Irreversible Pulpitis Secondary to Dentigerous Cyst

Abstract: Dentigerous cysts are uncommon, yet are being reported with increasing frequency in the veterinary literature. Dentigerous cysts are a type of benign odontogenic cyst associated with impacted teeth, most commonly the mandibular first premolar tooth. Significant bone destruction can occur secondary to the expansion of a dentigerous cyst. The expanding cyst can lead to pathology of neighboring teeth, which can include external root resorption or pulpitis. Intraoral dental radiographs are imperative to properly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
(111 reference statements)
1
2
0
3
Order By: Relevance
“…In the present study the mandibular first premolar tooth was not only the most commonly diagnosed unerupted tooth (85 of 108 unerupted teeth), but was also most commonly associated with cyst development (41 of 48 dentigerous cysts). This is also in agreement with the data extrapolated from the literature, with cysts described in association with 49 out of 71 (69%) reported unerupted first premolar teeth (13, 14, 20, 29, 50, 54, 57, 58, 60, 70). Interestingly, six of eight unerupted canine teeth in the present study were associated with a cystic lesion, one with a neoplastic lesion, and one showed a radiographically equivocal pericoronal appearance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study the mandibular first premolar tooth was not only the most commonly diagnosed unerupted tooth (85 of 108 unerupted teeth), but was also most commonly associated with cyst development (41 of 48 dentigerous cysts). This is also in agreement with the data extrapolated from the literature, with cysts described in association with 49 out of 71 (69%) reported unerupted first premolar teeth (13, 14, 20, 29, 50, 54, 57, 58, 60, 70). Interestingly, six of eight unerupted canine teeth in the present study were associated with a cystic lesion, one with a neoplastic lesion, and one showed a radiographically equivocal pericoronal appearance.…”
Section: Discussionsupporting
confidence: 92%
“…The development of dentigerous cysts is commonly associated with unerupted teeth in humans and animals (68, 69). Several veterinary case reports (21, 25, 28–30, 32–34, 37, 42, 50, 5254, 57, 60, 70) and a few retrospective studies (13, 14, 20) describe dentigerous cysts associated with unerupted teeth in dogs. Cysts may develop by accumulation of fluid between the REE and enamel, or between the layers of enamel epithelium itself, but the exact pathogenetic mechanism remains unclear (71).…”
Section: Discussionmentioning
confidence: 99%
“…O cisto dentígero é o cisto odontogênico benigno mais comum em cães. Todavia, sua incidência é baixa, e está associado a dentes inclusos, ocorrendo principalmente no primeiro pré-molar mandibular de cães braquicefálicos e de pequeno porte (BELLEZZA et al, 2008;KUYAMA et al, 2009;D`ASTOUS, 2011;MACGEE et al, 2012;HONZELKA et al, 2014;MACGEE, 2014;VOELTER-RATSON et al, 2015;REQUICHA et al, 2015;BABBITT et al, 2016;HOLLY et al, 2018;HOYER et al, 2016;PERRY, 2017).…”
Section: Introductionunclassified
“…Os cistos dentígeros podem alcançar tamanhos significativos durante sua lenta expansão, levando a fraturas patológicas decorrentes de destruição óssea, invasão da cavidade nasal, reabsorção ou problemas endodônticos em dentes vizinhos, e podem em alguns casos se tornar malignos (D`ASTOUS, 2011;MACGEE et al, 2012;MACGEE, 2014;MOORE;NIEMIEC, 2014;VOELTER-RATSON et al, 2015;NIEMIEC, 2015;BABBITT et al, 2016;PERRY, 2017;THEYSE, 2017).…”
Section: Introductionunclassified
See 1 more Smart Citation